Evaluation of Anti-Inflammatory and Antibacterial Properties of Photo-Thermal Hydrogel as Dual Functional Platform for Management of Periodontitis - Mai Z; Mai Y; Huang X; Ning S; Liao H (International Journal of Nanomedicine, 2025)
Zhisong Mai,1 Yuying Mai,1 Xianxian Huang,1 Shipeng Ning,2 Hongbing Liao3 1Department of Prosthodontics, College of Stomatology, Guangxi Medical University, Nanning, Guangxi, 530021, People’s Republic of China; 2Research Center of Nanomedicine Technology, the Second Affiliated Hospital of Guangxi Medical University, Nanning, 530000, People’s Republic of China; 3Guangxi Key Laboratory of Oral and Maxillofacial Rehabilitation and Reconstruction, College of Stomatology, Guangxi Medical University, Nanning, Guangxi, 530021, People’s Republic of ChinaCorrespondence: Hongbing Liao, Email hongbing_liao@gxmu.edu.cnBackground: Periodontitis, one of the most common oral diseases caused by bacterial infection which affects gums, periodontal ligament and alveolar bone, is a leading cause of tooth loss in adults. Current clinical treatments, such as scaling or antibiotics, often result in incomplete biofilm removal or can contribute to drug resistance.Methods: To address these limitations, a nanozyme comprising platinum, copper, and selenium was developed, which was then incorporated into a thermoresponsive hydrogel.Results: When applied to periodontal pockets and exposed to 808 nm laser irradiation, the hydrogel became soft, dissolving to release the nanozyme. This nanozyme demonstrated superoxide dismutase (SOD)-like and catalase (CAT)-like activity, reducing excess reactive oxygen species (ROS) while displaying strong antibacterial and anti-inflammatory effects.Conclusion: This photothermal nanozyme hydrogel showed excellent biocompatibility and has the potential to overcome the challenges of current periodontitis treatments.Keywords: thermosensitive, photothermal therapy, hydrogel, periodontitis